Meningkatkan Minat Baca dengan Membangun Budaya Literasi Pada Anak Panti - Bengkel; Alfira Utami Isnaini (Yayasan Literasi Sains Indonesia, 2022)
Literacy activities are becoming increasingly vital and are being implemented on a large scale. Literacy is defined as the capacity to read and write in general. Literacy, on the other hand, is more than just reading and writing; it also encompasses the ability to utilise knowledge sources in print, visual, digital, and auditory formats. Early childhood is the most essential stage for the creation of children's knowledge and conduct, so literacy activities must begin then. Children have a good recall at this age because their personalities are undeveloped, making it simple for them to get caught up in behaviors that are common in everyday life. As a result, PKL I was carried out at the Sinar Damai Sejahtera Orphanage Foundation in order to help one of the children who lacked interest in reading and learning develop a literacy culture from an early age. The micro intervention method is used in the helping process (case work). As indicated by the rise of children's excitement for learning and interest in reading, the goal of this activity was reported to be met.